The p53–PUMA axis suppresses iPSC generation - Li, Yanxin (Nat Commun, 2013)
Mechanisms underlying the reprogramming process of induced pluripotent stem cells remain poorly defined. Like tumorigenesis, generation of induced pluripotent stem cells was shown to be suppressed by the Trp53 (p53) pathway, at least in part via p21(Cdkn1a) (p21)-mediated cell cycle arrest. Here we examine the role of PUMA, a pro-apoptotic mediator of p53, during somatic reprogramming in comparison to p21 in the p53 pathway. Using mouse strains deficient in these molecules, we demonstrate that PUMA is an independent mediator of the negative effect of p53 on induced pluripotent stem cell induction. PUMA deficiency leads to a better survival rate associated with reduced DNA damage and fewer chromosomal aberrations in induced pluripotent stem cells, whereas loss of p21 or p53 results in an opposite outcome. Given these new findings, PUMA may serve as a distinct and more desirable target in the p53 pathway for induced pluripotent stem cell generation, thereby having important implications for potential therapeutic applications of induced pluripotent stem cells.